Design of Battery Charging System with CC-CV Method Using Interleaved Buck-Boost Converter - I Gusti Agung Ayu Devi Anjani; Moh Zaenal Efendi; Ony Asrarul Qudsi (Journal of Electrical Technology UMY, 2023)
The transition of renewable energy has become an interesting issue and a worldwide concern that is frequently discussed. Solar panels are regarded to have the most potential in tropical areas like Indonesia. However, weather and sunlight intensity have a substantial impact on the amounts of electricity generated by solar panels. Therefore, a battery which functions as a backup supply is required. Lead acid batteries are used in numerous applications. The performance of lead-acid battery is commonly influenced by temperature and charging time, which makes it vulnerable to overcharging. Multistage charge methods, namely Constant Current-Constant Voltage (CC-CV), are used to extend battery life, reduce charging time, and avoid the risk of overcharging. Fuzzy Logic Controller (FLC) is used to adjust charging current and voltage on the battery based on the setpoint. Based on the CC-CV charging system simulation results, a constant current value can be obtained when the CC condition is 4.5 A, and a transition to the CV condition occurs when the voltage value on the battery reaches 14.4 V. When the battery reaches its maximum capacity, the current is reduced to 3% of the battery’s capacity. The rate of fully charged current triggers the relay to turn on, to ensure that the charging process has been completed.